The Role of Artificial Intelligence in Enhancing English Language Teachers’ Professional Competence - Nozima Sayfiddinova (Indonesian Journal Publisher, 2025)
This study aims to examine the role of artificial intelligence (AI) in enhancing the professional competence of English language teachers in the context of digital education. The research employs a qualitative descriptive approach supported by literature analysis and reflective examination of AI-based teaching practices, including intelligent tutoring systems, automated assessment tools, and chatbots. Data were obtained from recent scholarly publications, empirical studies, and documented educational practices related to AI integration in language teaching. The findings reveal that AI contributes significantly to strengthening teachers’ professional competence by enhancing pedagogical content knowledge, supporting personalized instruction, improving assessment efficiency, and promoting reflective teaching practices. The study also identifies key challenges, such as the need for digital literacy, ethical considerations, and balanced human–AI collaboration. Overall, the results indicate that AI serves as a powerful supportive tool for continuous professional development and innovation in English language teaching.